THE Analysis of Factors Associated with Anemia Among Adolescent Girls - Shinta Novelia; Rukmaini; Indah Purnama Sari (KHD-Production, 2022)
The World Health Organization (WHO) in the worldwide prevalence of anemia in 2015 showed that the prevalence of anemia in the world ranges from 40-88%. In Southeast Asia, 25-40% of adolescent girls have mild and severe anemia. Based on the results of the Indonesian Demographic and Health Survey (SDKI) in 2017, the prevalence of anemia in children aged 5-12 years in Indonesia is 23%. The purpose of this study is to find out the Factors Associated with Anemia in Adolescent Girls in the Kampung Sawah South Tangerang. This research method uses a type of quantitative research with cross sectional design studies. The sample technique in the study was purposive sampling, with a sample of 75 adolescents. The instruments used are questionnaires and GCHb Easy Touch, data analyzed using the chi-Square Test. The results showed that 58.7% of adolescents had anemia and 41.3% of adolescents did not have anemia. There was a relationship between family income (p = 0,000), knowledge (p = 0,000), food boosting iron absorption (p = 0.000), nutritional status (p = 0.005) and physical activity (0.000) with anemia among adolescent girls. There was no association between iron absorption-inhibiting foods (p=0.603), and menstruation (p=0.397) and anemia in adolescent girls. Conclusions and suggestions that can be given are anemia caused by low family income, low knowledge, not consuming foods that encourage iron absorption, abnormal nutritional status, and adolescents who carry out strenuous activities, it is expected that the school will coordinate with the Health Centre to hold health counseling activities, especially regarding adolescent anemia periodically, conducting early detection to find out the signs and symptoms of anemia